Sustainable Development Management of Local Territories in the Eastern Ukraine in Conditions of Military Conflict: Identification Criteria - Rohozian, Yuliia; Hrechana, Svitlana; Kuzmenko, Olena; Derzhak, Nataliia; Kuchmenko, Vitalii; Plietnov, Mykhailo (European Journal of Sustainable Development, 2020)
Decentralization, which has begun and continues in Ukraine, has raised the living standards of local people to a new level by updating tools and methods of managing the sustainable development of such territories, updating a particularly balanced approach to planning and finding reliable sources. In this context, it is advisable to identify qualitatively the local area, which is not only a guarantee of their subjectivity and sustainability, but also the basis for the strategies forming for their socio-economic development, the realism and effectiveness of which is based on sustainable development management as well as administrative and financial capacity of communities. However, as practice has shown, most local areas, although willing to identify their unique features, but do not know how to do it, because the current legal field in Ukraine does not regulate the procedure and criteria for such identification. This article was an attempt to research the managerial possibilities of creating a positive image of the territory through the sustainable development and choice of appropriate assessment parameters – the criteria for identifying the amalgamated territorial communities of Ukraine as local territories. As a result of the research, a model list of such criteria is proposed, which is sufficiently universal to determine the unique and typical characteristics of any territories, and also contains a specific subsystem that allows reflecting the individual features of territories close to the armed conflict zone in the Eastern Ukraine. Using this list will allow communities to form one or more images of the local area: from formal (real) to imaginary and special. It will help improve the results of communities and territories identification, the foundation for the sustainable development with marketing measures to promote communities as well as the formation of management decisions for their strategic and sustainable development, which will be best adapted to the realities of the current armed conflict. Keyword: sustainable development management, identification criteria, local territories, amalgamated territorial communities, military conflict